Unreasonable doubt : circumstantial evidence and an ordinary murder in New Haven - Thompson, Norma, 1959- (University of Missouri Press, 2006)
"A murder trial ends in a hung jury because of the reasonable doubt of a few jurors who, faced with circumstantial evidence, refuse to judge the accused. Thompson confronts this evasion of judgment through the reexamination of the works of Faulkner, Austen, Tocqueville, Plato, and Aristotle"--Provided by publisher